AKR1D1 regulates glucocorticoid availability and glucocorticoid receptor activation in human hepatoma cells. Issue 189 (May 2019) - Nikolaou, Nikolaos; Gathercole, Laura L.; Kirkwood, Lucy; Dunford, James E.; Hughes, Beverly A.; Gilligan, Lorna C.; Oppermann, Udo; Penning, Trevor M.; Arlt, Wiebke; Hodson, Leanne; Tomlinson, Jeremy W.
Highlights: AKR1D1 regulates glucocorticoid availability in human hepatoma cells. AKR1D1 regulates glucocorticoid receptor activation in human hepatoma cells. 5α-reductase inhibitors are not able to block AKR1D1 activity in vitro . Abstract: Steroid hormones, including glucocorticoids and androgens, have potent actions to regulate many cellular processes within the liver. The steroid A-ring reductase, 5β-reductase (AKR1D1), is predominantly expressed in the liver, where it inactivates steroid hormones and, in addition, plays a crucial role in bile acid synthesis. However, the precise functional role of AKR1D1 to regulate steroid hormone action in vitro has not been demonstrated. We have therefore hypothesised that genetic manipulation of AKR1D1 has the potential to regulate glucocorticoid availability and action in human hepatocytes. In both liver (HepG2) and non-liver cell (HEK293) lines, AKR1D1 over-expression increased glucocorticoid clearance with a concomitant decrease in the activation of the glucocorticoid receptor and the down-stream expression of glucocorticoid target genes. Conversely, knockdown of AKR1D1 using siRNA decreased glucocorticoid clearance and reduced the generation of 5β-reduced metabolites. In addition, the two 5α-reductase inhibitors finasteride and dutasteride failed to effectively inhibit AKR1D1 activity in either cell-free or hepatocellular systems. Through manipulation of AKR1D1 expression and activity, we have demonstrated its potent ability to regulate glucocorticoid availability and receptor activation within human hepatoma cells. These data suggest that AKR1D1 may have an important role in regulating endogenous (and potentially exogenous) glucocorticoid action that may be of particular relevance to physiological and pathophysiological processes affecting the liver.